Looking at ijk = -1, i'm trying to fully understand how to find individual values.
i appears easy: i(ijk) = -1(i) -> i2jk = -i -> -jk = -i -> jk = i
Trying to find j is problematic: j(ijk) = -1(j) -> ij2k = -j -> -ik = -j -> ik = j
That's wrong, it should be ki = j and ik = -j
Can someone point out what i'm doing wrong here?
It seems that the ij2k = -j -> -ik = -j step is wrong, but i don't know how to handle i-k = -j
Am i just free to arbitrarily re-arrange it to -ki = -j, that seems wrong somehow....